2020
DOI: 10.1080/21655979.2020.1839216
|View full text |Cite
|
Sign up to set email alerts
|

Correlation in gene expression between the aggravation of chronic obstructive pulmonary disease and the occurrence of complications

Abstract: Aggravation of the chronic obstructive pulmonary disease (COPD) often leads to a slew of complications, but the correlation between COPD aggravation and the complications on the basis of molecular level remains unclear. In this study, gene expression profiles of COPD in patients at early and aggravation stages were collected and differentially-expressed genes were selected. Meanwhile, gene expression data implicated in COPD complications were analyzed to establish a regulatory network of COPD aggravation and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…A study showed that the LCK protein is a constitutive component of the T-cell receptor (TCR) ( Jury et al., 2003 ). LCK can regulate the TCR’s function to recognize pathogens’ antigens and generate immune responses ( Cai et al., 2020 ). Based on interconnected cues, we inferred that MMP12 was further involved in the underlying mechanisms of LUSC by participating in T lymphocyte-dominated adaptive reactions.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the LCK protein is a constitutive component of the T-cell receptor (TCR) ( Jury et al., 2003 ). LCK can regulate the TCR’s function to recognize pathogens’ antigens and generate immune responses ( Cai et al., 2020 ). Based on interconnected cues, we inferred that MMP12 was further involved in the underlying mechanisms of LUSC by participating in T lymphocyte-dominated adaptive reactions.…”
Section: Discussionmentioning
confidence: 99%